2018
DOI: 10.1016/j.jweia.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Generating atmospheric turbulence using passive grids in an expansion test section of a wind tunnel

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 55 publications
6
27
0
4
Order By: Relevance
“…In general, for z/D > 0.2, I u~Iw , meaning that the turbulence is rather uniform and isotropic, close to grid turbulence and therefore easy to be reproduced in wind tunnels. This shows that it could be possible to use grid turbulence in wind tunnel testing for practitioners to design and test wind turbines in turbulent flows [40]. Such isotropic behaviour is not present at lower heights (z/D < 0.2), where the longitudinal component is significantly higher than the vertical one.…”
Section: Turbulence Intensitymentioning
confidence: 94%
“…In general, for z/D > 0.2, I u~Iw , meaning that the turbulence is rather uniform and isotropic, close to grid turbulence and therefore easy to be reproduced in wind tunnels. This shows that it could be possible to use grid turbulence in wind tunnel testing for practitioners to design and test wind turbines in turbulent flows [40]. Such isotropic behaviour is not present at lower heights (z/D < 0.2), where the longitudinal component is significantly higher than the vertical one.…”
Section: Turbulence Intensitymentioning
confidence: 94%
“…The grid characteristics are the following; the width of the bars b = 5 cm, mesh size M = 35 cm (i.e., the distance between the centreline of the bars), and the downstream distance from the grid to the section where measurements were performed x = 5 m, see Figure 12. The x/M > 14 rate assures a homogeneous and isotropic turbulent flow [34], whose main characteristics are a turbulence intensity of I = 4.2% and an integral length L = 0.2 m.…”
Section: Wind Tunnel Experimentsmentioning
confidence: 99%
“…A recent and synthetic review of these techniques can be found in the paper of Vita et al [2]. According to literature [2][3][4], turbulence grid generation is the most effective and reliable technique to produce turbulence in a wind tunnel. These grids can be classified in three categories: passive grids, active grids and fractal grids.…”
Section: Contextmentioning
confidence: 99%